Illegal drugs in the UK: Is it time for considered legalisation to improve public health?. (April 2021) - Dalgarno, Phil; O'Rawe, Steve; Hammersley, Richard
This paper investigates options available to policy makers responding to the challenges of drug use in modern society, focussing on the UK. It investigates the failings of prohibition policy that has driven historic reactions to drugs, drug use and drug users globally, nationally and locally. This policy paradigm has been largely destructive and counter-productive and has led to a whole host of health and social problems. The authors have approached their investigation from a public health perspective, free from moral biases that have driven many policy initiatives until now. Many countries and regions of the world are rejecting prohibition as they move towards public health models in opposition to criminal justice responses, and this trend is continuing. Four policy models are examined; prohibition as the status quo; extension of prohibition to include alcohol and other drugs; decriminalisation; legalisation and regulation of all drugs. Each of these policy options are contested; none have universal support. However, given careful consideration, this paper proposes that our only way out of the public health and criminal justice crises that have been driven by drug policy globally is to adopt the more contentious option of legalisation and regulation of all drugs commonly used non medically.